Artificial Intelligence and the Transformation of Internal Audit in the Banking Sector - Alami Gholami , El Ghali; Lotfi , Mohamed (Revue Internationale des Sciences de Gestion, 2026)
Artificial Intelligence (AI) is transforming the banking sector, particularly internal audit functions. This study analyzes how AI enhances internal audit effectiveness and identifies associated risks. A systematic literature review based on PRISMA methodology was conducted using Scopus, Web of Science, and Google Scholar. The results show that AI improves efficiency, fraud detection, and risk management, but raises governance and ethical challenges.